2012
DOI: 10.1108/17511341211188646
|View full text |Cite
|
Sign up to set email alerts
|

The first documents of emancipated African American management

Abstract: PurposeThis paper aims to trace the historical roots of African American management by examining managerial practices and experiences described in the letters of Benjamin Thornton Montgomery, a former slave who eventually became manager and, ultimately, owner of the Hurricane plantation.Design/methodology/approachThe method used is the historical archival method of analysis, primarily the examination of a series of letters written by Montgomery during the 1865‐1870 time periods. These letters, which document t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…The Freedmen's Bureau was a governmental organization in the War Department that focused on transitioning former slaves into U.S. society. Narratives from ex-slaves during that time indicate that Freedmen's Bureau's officials often displayed racist attitudes that often perpetuated the oppression and discrimination of the freed slaves (Jones, Novicevic, Hayek, & Humphreys, 2012). Although social services were a part of the Freedmen's Bureau, the beginning of social work as a profession is often marked by the beginning of Charity Organization Societies and settlement houses, which focused primarily on helping European immigrant groups' transition into society.…”
Section: Introductionmentioning
confidence: 98%
“…The Freedmen's Bureau was a governmental organization in the War Department that focused on transitioning former slaves into U.S. society. Narratives from ex-slaves during that time indicate that Freedmen's Bureau's officials often displayed racist attitudes that often perpetuated the oppression and discrimination of the freed slaves (Jones, Novicevic, Hayek, & Humphreys, 2012). Although social services were a part of the Freedmen's Bureau, the beginning of social work as a profession is often marked by the beginning of Charity Organization Societies and settlement houses, which focused primarily on helping European immigrant groups' transition into society.…”
Section: Introductionmentioning
confidence: 98%
“…The story of the founding of Mound Bayou, Mississippi ‘is a tale that seems to defy even its own enduring legacy …’ (Rosen, 2011: 119). The idea for the town was partly born out of Isaiah Montgomery’s embrace of the lessons that he learned from his father Ben Montgomery, a slave, and unlikely business partner of Joseph Davis (Jones et al., 2012), a plantation owner (and the brother of Jefferson Davis, the President of the Confederate States of America during the American Civil War from 1861 to 1865). Rosen (2011) suggests that much of Isaiah’s philosophy was influenced by Joseph Davis’ interest in the collective ideas of Robert Owen.…”
Section: Mound Bayoumentioning
confidence: 99%
“…By examining paternalistic leadership through the lens of a slave owner, we can better understand unique dimensions of a concept previously unstudied. Jones et al (2012) examined the letters of a former slave who eventually became manager of a plantation. As they traced the historical roots of African American management, they found that the former slave's management practices incorporated classical management principles.…”
Section: Slaverymentioning
confidence: 99%